Answer:
C. x = 1
Explanation:
To solve this problem the best way is to use the quadratic formula. First make everything equal to 0 by adding 3 to both sides.
3x^2 - 6x + 3 = 0
The quadratic formula is:
. Substitute the values of a, b, and c into the formula. Keep in mind:
![(-(-6)\pm√((-6)^2-4(3)(3)) )/(2(3)) \rightarrow (6\pm√(36-4(9)) )/(6) \rightarrow (6\pm√(0) )/(6) \rightarrow (1\pm0)/(1) \rightarrow 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i3vnr9dstejibyysxt5sectd5os0eyrnja.png)
Therefore, x = 1.